Kršitev simetrije CP - Šadl, Mitja (Matrika, 2016)
This article presents the CP violation, which is necessary for the creation of a world, where matter dominates antimatter. Initially, evolution of the universe since the Big Bang, when matter and antimatter were in equal amounts, is described, followed by the presentation of observations, which show the domination of matter. Later on CP violation is explained, using the Sakharov conditions. In conclusion, the Belle experiment is discussed, as its results have contributed to confirmation of CP violation.
Keywords: CP violation; fizika osnovnih delcev; kršitev simetrije CP; particle physics; Standard model; Standardni model